IDENTIFIKASI SAMPAH LAUT (MARINE DEBRIS) DI PESISIR KELURAHAN MOTTO, KECAMATAN LEMBEH UTARA, KOTA BITUNG, SULAWESI UTARA - Manengkey, Jenny I; Saranga, Rudi; Putri, Elsari Tanjung; Antou, Lusje (JURNAL BLUEFIN FISHERIES, 2022)
Marine debris is an important issue in environmental problems that can have a negative impact on an area. Motto village, Bitung is one of the centers of activity in the capture fisheries sector. This study aims to identify the characteristics types and density of marine debris found on the coastal of Motto village, Bitung. The research method is through observation and measurement of the type and composition of the weight of marine debris. Data were analyzed using quantitative descriptive analysis. The result showed that the characteristics of the type of marine debris found were macro-sized which divided into 3 categories, namely organic waste, plastic inorganic waste and non-plastic inorganic waste. The density of the amount and weight of marine waste that dominates is the type of organic waste in the form of leaves, namely 0.630 items/m2 and 31.372 grams/m2. The percentage of the relative density of marine debris on the coastal of Motto Village is 69% organic waste, 26% plastic inorganic waste and 5% inorganic waste. The percentage of heavy relative density of marine debris found in the Coastal Village of Motto is organic waste by 84%, plastic inorganic waste by 13% and inorganic non-plastic waste by 3%.